A Study of Dentists about Their Knowledge and Practice of Dentine Hypersensitivity - Izhar, Faisal; Nazir, Muhammad Ashraf; Majeed, Abdul; Almas, Khalid (European Journal of Dentistry, 2019)
Objective The aim of this study was to evaluate the knowledge and practice about dentine hypersensitivity (DH) among dental practitioners.Materials and Methods A pilot-tested questionnaire was sent to practicing dentists (n = 588) working in private and public sectors in Lahore, Pakistan. The questions assessed dentists’ knowledge about type of pain and predisposing factors of DH. The dentists were asked about their preferred methods of diagnosing and managing the condition.Statistical Analysis Basic statistics, chi-squared test, and multivariate logistic regression were performed.Results Most dentists (64.3%) reported examining one to five patients with DH per week in their dental clinics. A large majority (85.4%) indicated DH as a stimulated short pain from a tooth. Recession of gums (96.6%), aggressive brushing (88.2%), and frequent use of teeth whitening procedures (83.1%) were most frequently reported predisposing factors of DH. Among most commonly used methods of diagnosis, spontaneous pain after the application of air blast was reported by 74.8% of the participants and followed by spontaneous patient report confirmed by dental examination (57.7%). Most widely used management approaches of DH included the use of fluoride products (96.2%), use of desensitizing potassium nitrate toothpastes (75%), and application of bonding agents (56.2%). Female versus male dentists (odds ratio [OR]: 7.79, p < 0.001) and private practitioners versus public dentists (OR: 7.34, p < 0.001) were more likely to examine greater number of patients with DH.Conclusion Dentists used various methods for diagnosing and managing patients with DH. Application of air blast to evaluate spontaneous pain and use of fluoride products were most widely used diagnostic and management preferences, respectively.
Keywords: dentine hypersensitivity; dentists; knowledge; diagnosis; management